Tradition in Ángela Segovia's "Amor divino": Medieval literature influence in contemporary poetry - Rodríguez Ramos, Laura (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This paper analyses the linguistic innovations in Ángela Segovia’s Amor divino. It also covers the importance of Literature tradition in her work, with special interest in the medieval one. Archaisms, phonetic variation and didactic prose structures are used by the Spanish poet. She updates and transforms in original some narrative strategies used centuries ago, paying great attention to orality and its textual implications. Furthermore, these mechanisms can also be observed in other poets born in the 80’s of the XX century, Segovia’s contemporaries, as Berta García Faet or Juan Andrés García Román.
Keywords: Poetry; poetry language; medieval literature; tradition